Textbook of Microbial Diversity - Koche, Dr. Dipak Kewalramji; Shirsat, Dr. Rupali Prakash (Textbook of Microbial Diversity, 2025)
The Textbook of Microbial Diversity is a comprehensive book that explores the diverse world of microorganisms. It covers various groups of microbes, such as bacteria, fungi, archaea, viruses, and protists, emphasizing their unique characteristics, classification, and ecological roles. The book often integrates information from microbiology, ecology, and genetics to offer a detailed understanding of how these organisms contribute to the environment, human health, and industrial applications. The key topics covered in this book include microbial classification and taxonomy, diversity of microbial life exploring the immense variety of microbial species found in different ecosystems, microbial ecology that discusses the fundamental interactions between microbes and their environment and their role in nutrient cycling, biotechnological applications of microbes in various sectors and outline of the use of various modern techniques require to study microbial diversity. The book aims to provide readers with a foundational understanding of microbial life and the methods used to study and appreciate its complexity and importance. It serves as a useful resource for degree students, researchers, and teachers interested in microbiology, botany, ecology, and other related fields.